Understanding the role of the anode on the polarization losses in high-temperature polymer electrolyte membrane fuel cells using the distribution of relaxation times analysis - Bevilacqua, N.; Schmid, M. A.; Zeis, Roswitha (Journal of Power Sources, 2020)
To investigate the role of the anode on the polarization losses of a High-Temperature Polymer Electrolyte Membrane Fuel Cell (HT-PEMFC), we analyzed impedance data using the Distribution of Relaxation Times (DRT) method. Thereby, we varied the operating conditions of the anode (humidification, nitrogen dilution, and carbon monoxide (CO) impurities) to study its impact on Nyquist plot and DRT spectrum. Humidification of the hydrogen was found to dilute phosphoric acid, which is visible in the DRT. Nitrogen dilution of the anode gas slightly increases the Mass Transport (MT) resistance. Furthermore, CO was added to anode gas fed and it impacts the impedance throughout the whole frequency range, specifically the medium and low-frequency range, typically assigned to ORR kinetics and oxygen MT. For a more detailed analysis of the impedance data, a reference electrode was employed to separate the overpotential caused by each electrode. The DRT spectrum of the anode exhibits only one peak at 1 kHz. In the presence of CO, a second peak arises corresponding to side-reactions occurring as the anodic half-cell potential increases. It was found that the cathode is affected by CO on the anode merely by the lowered cell potential and not by CO directly.
CRIS-Team Scopus Importer:2023-08-01
Keywords: Carbon monoxide (CO); Distribution of relaxation times analysis (DRT); Electrochemical impedance spectroscopy (EIS); High-temperature polymer electrolyte membrane fuel cell (HT-PEMFC); Reference electrode